Overview of prevalence of malocclusions in primary dentition - Golovachova, Elene; Mikadze, Tinatin; Kalandadze, Manana (Caucasus Journal of Health Sciences and Public Health, 2018)
The perfect primary dentition is the predictor of future normal permanent occlusion. One of the main roles of primary dentition is to determine permanent occlusion and keep spaces for erupting teeth. The knowledge of different signs and characteristics of primary dentition, gives us opportunity to predict future changes and disorders in permanent dentition development. Early diagnosis, preventive measures and early treatment may let us avoid the further development of maxillofacial anomalies, deformities and functional disorders. Also at early age we can manage facial growth, thus avoid physiological disturbances associated with malocclusions and maxillofacial anomalies